Improvement of Self-sensing Piezoelectric Actuator Control Using Permittivity Change Detection - Yusuke ISHIKIRIYAMA; Takeshi MORITA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2010)
We present a self-sensing control method of piezoelectric actuators that compensate the hysteresis characteristics by using the linear relationship between the permittivity change and the piezoelectric displacement. In this article, improvement of this method is described. Increasing the frequency of the voltage for a permittivity detecting, the sensitivity of the permittivity detection was improved and the accuracy of the displacement sensing could be enhanced. In addition, by applying this self-sensing method, we tried to overcome the creep phenomenon that is a peculiar problem of piezoelectric actuators.